(untitled) (Medico Legal Update, 2021)
Human papillomavirus (HPV) is a DNA tumor virus that is the primary cause of sexually transmitted infections (STIs). The present study aimed to to evaluate the Effect of nursing guideline about genital Human papilloma virus infection on Knowledge and attitudeof female university students’. Sample Type: A convenience sampling technique. Research design: Quasi-experimental design was used in this study. Setting: at Faculty of nursing in Alexandria University. Sample Size: Total sample size was two hundred seventy five (275) female students. Data was collected by, 1): An Arabic structured Interviewing Questionnaire. 2) Follow up sheet and 3) likert Scale.Results: the result of the present study findings had revealed that a highly significant improvement in total knowledge and attitude among the studied sample pre–nursing guideline compared to immediate and 6 months post- nursing guideline P = < 0.01. The majority of studied sample satisfied with the advanced knowledge included in the nursing guideline. Conclusion: The present study findings concluded that a significant improvement among studied sample’ knowledge andattitude after implementation of guideline. Recommendations: There is a need for awareness campaigns to improve the poor knowledge of female university students in order to change behavior and reduce risk of HPV infection so that they will take the HPV vaccine. As a step towards prevention of cervical cancer.